Reliability and concurrent validity of a functional electromechanical dynamometer device for the assessment of movement velocity - Rodriguez-Perea, A.; Jerez-Mayorga, D.; Garcia-Ramos, A.; Martinez-Garcia, D.; Chirosa Rios, L. J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2021)
The aims of the study were (i) to determine the reliability and concurrent validity of a functional electromechanical dynamometer (FEMD) to measure different isokinetic velocities, and (ii) to identify the real range of isokinetic velocity reached by FEMD for different prescribed velocities. Mean velocities were collected simultaneously with FEMD and a linear velocity transducer (LVT) in two sessions that were identical, consisting of 15 trials at five isokinetic velocities (0.40, 0.60, 0.80, 1.00, and 1.20 m·s-1) over a range of movement of 40 cm. The results obtained using each method were compared using Paired samples t-tests, Bland-Altman plots and the Pearson`s product-moment correlation coefficient, while the reliability was determined using the standard error of measurement and coefficient of variation (CV). The results indicate that the mean velocity values collected with FEMD and LVT were practically perfect correlations (r > 0.99) with low random errors (<0.06 m·s-1), while mean velocity values were systematically higher for FEMD (p < 0.05). FEMD provided a high or acceptable reliability for mean velocity (CV = 0.24%), time to reach the isokinetic velocity (CV range = 1.68%-9.70%) and time spent at the isokinetic velocity (CV range = 0.53%-8.94%). These results suggest that FEMD offers valid and reliable measurements of mean velocity during a fixed linear movement, as well as a consistent duration of the isokinetic phase. FEMD could be an appropriate device to evaluate movement velocity during linear movements. More studies are needed to confirm the reliability and validity of FEMD to measure different velocity metrics during more complex functional exercises.